THE RESULTS OF THE FORECAST OF THE MAIN TECHNOLOGICAL INDICATORS OF THE DEVELOPMENT OF THE OIL AND GAS CONDENSATE FIELD EASTREN ISPANLI (American Journal of Research in Humanities and Social Sciences, 2023)
The results of calculation of the main technological indices of the development of Sharqiy Ispanli oil and gas condensate deposit are presented for various options, differing in the sequence of oil and gas sampling. It is shown that during the development of the field with the use of vertical wells and the faces of producing wells, free gas will break through. It is recommended to drill multi-hole wells with horizontal trunks.